Research status and hotspots in the surgical treatment of tremor in Parkinson’s disease from 2002 to 2022: a bibliometric and visualization analysis - Zeng, Jingchun; Chu, Hui; Lu, Yiqian; Xiao, Xi; Lu, Liming; Li, Jingjing; Lai, Guoan; Li, Lisha; Lu, Lihong; Xu, Nenggui; Wang, Shuxin (Frontiers in Aging Neuroscience, 2023)
Objective This study aims to investigate the research status and hotspots of surgical treatment for tremor in Parkinson’s disease (PD) from 2002 to 2022, utilizing bibliometric and visual analysis. Additionally, it aims to offer insights into future research trends in this field. Methods This study collected publications on the surgical treatment of tremor in PD from 2002 to 2022 using the Web of Science (WOS) database. CiteSpace, VOSviewer, and Scimago Graphica were employed to quantify the number of publications and analyze the bibliographic information networks, including the contributions of countries/cities, authors, keywords, and co-cited references. Results A total of 2,815 publications were included in the study, revealing that 541 scientific institutions experienced an increase in publications from 2002 to 2022. Michael Okun emerged as the most productive author, and the United States emerged as the leading hub for research. The study identified 772 keywords. Noteworthy citation bursts and long-term activity were observed in pallidotomy, bilateral stimulation, and focused ultrasound thalamotomy. The top 10 highly co-cited references comprised eight deep brain stimulation (DBS) studies (including two follow-up studies and six randomized controlled trials), one randomized controlled trial on focused ultrasound, and one consensus on tremor. Conclusion This study uses an in-depth and systematic bibliometric and visualization analysis to visualize the evolution of research and identify emerging hotspots. The identified hotspots are as follows: Firstly, DBS has received significant attention and widespread recognition as a surgical treatment for tremor in PD. Secondly, there are various key aspects to consider in DBS, such as operative indications, operative targets, and surgical protocols. Lastly, magnetic resonance-guided focused ultrasound (MRgFUS) has emerged as a promising treatment option in the surgical management of tremor in Parkinson’s disease. This research also provides insights into the phenomenon of these hotspots, offering valuable prompts and reminders for further research.